Electronic transport mechanism of CdTe nanocrystalline - Abd El-sadek, M. S.; Yahia, I. S.; Salem, A. M. (Elsevier Science Sa, 2011)
CdTe nanocrystalline powder was synthesized by chemical process. The structure of CdTe nanocrystalline was investigated by means of X-ray diffraction (XRD) technique, energy-dispersive X-ray analysis (EDAX) spectrum and transmission electron microscopy (TEM). The selected area electron diffraction (SAED) study confirms the crystallinity of the CdTe nanocrystalline. Some structural parameters such as the mean crystallite size, the dislocation density and the strain were calculated. The temperature dependence of the dc and ac conductivity was measured in the temperature range 293-423 K. It was found that the dc conductivity is thermally activated type. Values of dc activation energy and the pre-exponential were determined. The ac conductivity was found to increase with increasing both the temperature and frequency and follows the power low. The frequency exponent s was found to decrease with increasing temperature. The correlated barrier hopping (CBH) model was found to be applying to the ac conductivity data. The maximum barrier height W-m and the density of localized states N(E-F) were calculated and equal to 0.47 eV and 8.82 x 10(22) to 1.43 x10(23) eV(-1) cm(-3), respectively. CdTe nanomaterial is a good candidate for semiconductor devices due to its high conductivity. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chemical Synthesis; TEM; EDAX; Debye-Scherrer powder method and electrical properties